Determination of Cd, Ni and V in Spices by Solid Sampling High-Resolution Continuum Source Graphite Furnace Atomic Absorption Spectrometry - Virgilio, Alex; Rego, Jardes F. [UNESP]; Barros, Ariane I. [UNESP]; Gomes Neto, Jose A. [UNESP] (Soc Brasileira Quimica, 2015)
This work describes a procedure for determination of Cd, Ni and V in spices by high-resolution continuum source graphite furnace atomic absorption spectrometry (HR-CS GF AAS) using direct solid sampling (SS). The use of Pd/Mg(NO3)(2) as modifier for Cd, and an additional air-assisted pyrolysis step allowed the use of aqueous calibration for all analytes. Accuracy was checked by analysis of certified reference materials (CRMs) and the results were in agreement to certified values at 95% confidence level (t-test). Eight samples of spices were analyzed by the proposed procedure and by inductively coupled plasma mass spectrometry (ICP-MS). The found concentrations were 88-233 ng g(-1) Cd, 113-2842 ng g(-1) Ni and 154-1007 ng g(-1) V, with precision generally better than 12%. Results obtained by the proposed procedure were in agreement with those obtained by microwave-assisted digestion and ICP-MS determination. The limits of detection were 0.2, 18 and 7 ng g(-1) for Cd, Ni and V, respectively.
Keywords: direct solid sampling; high-resolution continuum source atomic absorption spectrometry; trace elements; food analysis; spices